A Cross-Sectional Study Comparing Traumatic Alopecia Among B-Boys and B-Girls to Other Dance Styles and Its Impact on Dance Performance and Health. Issue 1 (March 2023) - Hall, Marshall; Lim, Henry; Kim, Suhhyun; Fulda, Kimberly G.; Surve, Sajid A.
Introduction: Breaking, often mislabeled as breakdancing in the media, is a dance style originating from the Bronx of New York in the early 1970s. A unique condition in this population is a form of alopecia known as "headspin hole, " or "breakdancer overuse syndrome" of the scalp. This form of hair loss may show a variety of patterns based on the activities of the dancer. The purpose of this study was to investigate the relationship between alopecia and breaking, the level of concern dancers have regarding hair loss, barriers to medical treatment, and how it affects their dancing. Methods: This was a cross-sectional study using an online survey. The survey addressed participants' demographics, hair, dancing styles, training, and health history. Questions about the effects of hair loss on the participants were also asked. Results: This study found that there was a significant difference in hair loss among breakers compared to non-breakers. This was not seen after controlling for age and sex. However, the concern for hair loss was significant even after controlling for these variables. Similarly, hair loss was significantly associated with the frequency of headspins. Despite these concerns, breakers were less likely to seek medical attention. Conclusions: This study showed that there are significant disparities in hair loss between breaking and other dance styles. Hair loss due to breaking has been shown to have significant effects on an individual's concerns, which may be compounded by the fact that this population is less likely to seek out medical care and have significantly greater substance use compared to the other dancers surveyed. Further research is necessary to investigate interventions to prevent and treat hair loss in this population and the means to decrease the gap in health care in the dance population.